Experimentally determining the sizes of water flow droplets entrained by high-temperature gases - Volkov R. S. Roman Sergeevich; Zhdanova A. O. Alena Olegovna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (Heat And Mass Transfer And Properties Of Working Fluids And Materials, 2015)
Title screen